OSNOVNO O GENEZI, SASTAVU I TROSENJU EOCENSKOG FLISA HRVATSKOG OBALNOG POJASA/SOME CHARACTERISTICS OF EOCENE FLYSCH GENESIS, COMPOSITION AND WEATHERING IN CROATIAN COAST BELT - Tosevski, Aleksandar; Grgec, Damir; Padovan, Bozo (Rudarsko-geološko-naftni zbornik, 2012)
The most common lithotypes of the Eocene flysch in the Croatian coast belt are breccias, conglomerates, (bio)calcirudites, (bio)calcarenites, sandstones, siltstones, shales and marls. Olistolithes also can be constitutive part of Eocene flysch. On the surface they can be mapped only in wider Split area. The mechanical weathering of the flysch rock mass is dominant in regard to the chemical weathering which is almost irrelevant for practical purposes. Mechanical weathering is caused by tectonic activities, and by repeated drying and wetting. It takes place in the engineering time, and not geological, which dictates the method of excavation, protection of slopes and construction pits in flysch rock masses. The quantity of the eroded material can extend 20000 m super( 3)krn super( 2)/ yr. Most subject to erosion are lithotypes which are dominantly made of clasts varying in size from silt to clay. The Slani Potok catchment in the Vinodol Valley mainly consists of Eocene flysch sediments. Its feature is that it represents the so far only known location in the External Dinarides in Croatia where the chemical weathering prevails in relation to mechanical, and that is caused by crystallization of the mineral tenardite. The precise determination of the weathering zone thickness of flysch, as well as other rock mass types is of great significance in geotechnical engineering. The weathering zone is mostly determined in four following ways: visually on the outcrop, by core mapping, analyzing the speed of primary seismic waves and analyzing the resistivity.